Ubiquitin dependent degradation of proteins modified by oxidation, deamidation and glycation: role in vision - Taylor, Allen (Henry Stewart Talks, 2007)
Description of cataract and AMD as the ultimate protein misfolding diseases, Lens development: a model for aging research, Photo-oxidative stress to the retina, Etiology, Environmental factors, Pathophysiology, Protein quality control, Ubiquitin pathway selectivity for oxidatively modified, glutathiolated, deamindated and glycated substrates, Clinical relevance
Reviewed at 2017/10/21